O poder e o sujeito em Michel Foucault: da sociedade disciplinar à sociedade de controle - Santana, Marival Baldoino de (2010)
This thesis addresses the problem of power and subjection of the subject. We seek to understand how Foucault understands power and its relationship with knowledge, which through its mechanisms acts as a force coercing, disciplining and controlling individuals. For Foucault, in modernity, as they were changing the social, political and economic relations, were also being produced new relations of power, more suited to each age, in every society. The power is exercised in the network and causes individuals to undergo, be subjected. Concurrently, the power, according to Foucault, it is also present in a positive, productive way. To the extent that individuals are transformed into a kind of transmission belt and reproduction, biopower emerges.